2020
DOI: 10.1021/acs.jmedchem.9b01502
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of a Potent and Selective Covalent Inhibitor for SRC Kinase That Targets a P-Loop Cysteine

Abstract: SRC is a major regulator of many signaling pathways and contributes to cancer development. However, development of a selective SRC inhibitor has been challenging, and FDA-approved SRC inhibitors, dasatinib and bosutinib, are multitargeted kinase inhibitors. Here, we describe our efforts to develop a selective SRC covalent inhibitor by targeting cysteine 277 on the P-loop of SRC. Using a promiscuous covalent kinase inhibitor (CKI) SM1-71 as a starting point, we developed covalent inhibitor 15a, which discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Our Src-SM1-71 crystal structure (PDB: 6ATE) revealed the Src p-loop in a kinked conformation (Rao et al, 2019). We subsequently showed that SM-1-71 could be optimized for Src inhibition by hybridization with dasatinib ( Figures 1A-D, Figure S1; Du et al, 2020). Here, we present formal biochemical, biophysical, and structural characterization of Src inhibition by DGY-06-116.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Our Src-SM1-71 crystal structure (PDB: 6ATE) revealed the Src p-loop in a kinked conformation (Rao et al, 2019). We subsequently showed that SM-1-71 could be optimized for Src inhibition by hybridization with dasatinib ( Figures 1A-D, Figure S1; Du et al, 2020). Here, we present formal biochemical, biophysical, and structural characterization of Src inhibition by DGY-06-116.…”
Section: Introductionmentioning
confidence: 72%
“…Altogether, our interpretation of these findings is that a strong reversible interaction is required to allow sufficient time for the ploop to sample a kinked conformation compatible with covalent bond formation. We speculate that that optimization of the interaction between the p-loop and compound may increase the inactivation rate, leading to further improvements in compound selectivity in biological systems, since covalent bond formation appears to be the major driver of selectivity (Du et al, 2020). One way to do this would be to increase the length of the linker to the covalent warhead so the p-loop does not have to kink.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The search for small molecules with an inhibitory activity toward Src kinases constitutes a growing field of study. Several compounds have entered clinical trials, with two compounds ultimately approved by the FDA: dasatinib, approved in 2006, and bosutinib, approved in 2012 [ 16 ]. However, dasatinib is known to inhibit over 40 kinases, while bosutinib inhibits over 45 kinases, making it impossible to use these compounds as selective mechanistic probes for Src-dependent pharmacology [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%